The Performance Management Factors Affecting on Employees’ Perceived Fairness in Private Sector Power Producers in Thailand - Sastrawaha, Panita; Akaraborworn, Chiraprapha (Human Resource and Organization Development Journal, 2021)
This paper aims to examine the issues related to Performance Management (PM) and Employees’ Perceived Fairness (EPF) using a holistic view to develop a model to explain this dyadic relationship. Four private sector power producers in Thailand agreed to be a part of this quantitative study using questionnaires to gather the data from 207 employees. Structural Equation Modeling (SEM) analysis was used to analyze the data gathered using the SPSS and AMOS program to assess what factors influence EPF and how well the proposed model can be used to explain this phenomenon. The results revealed that Performance Management Practices (PMP) and Perceived of Organizational Culture (OC), as perceived by employees, have a positive direct effect on EPF, while Relationship with Supervisor (RWS) has a negative significant effect on EPF. The proposed model suggests that to enhance EPF, PMP and OC should be integrated designed and implemented, supervisor should also be aware that their behaviors and their interactions with employees importantly effect on EPF. Both PMP and OC should be continuously assessed and adjusted to ensure an alignment of the two with organization’s directions and critical success factors, organization’s characteristics, organization’s visions, values, and strategies and organization’s members.